Durvalumab consolidation therapy in a patient with stage IIIB unresectable NSCLC harboring a MET exon 14 splice site alteration. (August 2021) - Cytryn, Samuel; Ferreira, Virginia; Boland, Patrick; Chachoua, Abraham; Sabari, Joshua
Highlights: Poor response to consolidation durvalumab in a patient with non-metastatic NSCLC, high PD-L1 expression, harboring a MET alteration. Targeted tyrosine kinase inhibitor therapy is not well studied in patients with non-metastatic, unresectable NSCLC harboring driver mutations. Patients with oncogene driven unresectable non-metastatic NSCLC may benefit from targeted inhibitor therapy, even if they also have high PD-L1 expression and have already received chemoradiotherapy. Abstract: Background: Recent literature has identified significant benefit of consolidation durvalumab following chemoradiotherapy in patients with unresectable non-small cell lung cancer (NSCLC). However, immunotherapy has demonstrated modest benefit in patients harboring oncogene driver mutations. While standard of care in metastatic oncogenic driven tumors is targeted tyrosine kinase inhibitors (TKIs), there is little data to guide treatment for patients who present with earlier stage unresectable disease, receiving chemoradiotherapy and have both high PD-L1 expression as well as concomitant actionable driver mutations. Clinical presentation: We report a patient who presented with stage IIIB lung adenocarcinoma with high PD-L1 expression (80%) for which she received definitive concurrent chemoradiotherapy with consolidation durvalumab. The patient quickly progressed and was found to harbor a MET exon 14 splice site alteration for which she received crizotinib and had a good response. Discussion: This case highlights the possibility that patients with non-metastatic, unresectable NSCLC with high PD-L1 expression and a concomitant driver mutation may benefit from targeted tyrosine kinase inhibitors rather than immune checkpoint inhibitor therapy.